The land characteristics as the determination of the agro ecological zone in the kambaniru watershed at kiritana village - Ena, Anggreni Wahyuninsy (Jounal of Enviromental Science Sustainable; Vol 2 No 1 (2021): Environmental Sustainability JournalDO - 10.31331/envoist.v2i1.1628, 2021)
xxxxxx